2021
DOI: 10.1002/slct.202103122
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Tetrasubstituted Cycloalkenes Bearing π‐Conjugated Substituents and Their Optical Properties

Abstract: We report the development of a new methodology for the preparation of cyclic tetrasubstituted alkenes with π-conjugated substituents. The synthesis of the target compounds was accomplished through the regioselective cross-coupling reaction of diphenyl bromocyclohexenyl phosphate with organo-zinc reagents. The procedure succeeded in the preparation of alkenes with two pyrene moieties. The absorption and photoluminescence spectra of the prepared compounds were measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…A similar approach has been employed for the preparation of 2-substituted cyclobutanones [ 82 ] and cyclobutenones [ 83 ]. Further studies have shown that aluminum chloride facilitates the Negishi reaction of cycloalkenyl diphenyl phosphates at room temperature [ 84 , 85 ].…”
Section: Organophosphates As Electrophiles In Transition-metal-cataly...mentioning
confidence: 99%
“…A similar approach has been employed for the preparation of 2-substituted cyclobutanones [ 82 ] and cyclobutenones [ 83 ]. Further studies have shown that aluminum chloride facilitates the Negishi reaction of cycloalkenyl diphenyl phosphates at room temperature [ 84 , 85 ].…”
Section: Organophosphates As Electrophiles In Transition-metal-cataly...mentioning
confidence: 99%
“…Tetrasubstituted alkenes, bearing a tetrasubstituted CC core, are widely used in material science, biomedicine, and chemistry . They also serve as useful chemical motifs for the synthesis of functional compounds . In particular, tetraphenylethylene (TPE), tetravinylethylene (TVE), tetraethynylethylene (TEE), and their derivatives have attracted much attention in the past several decades.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Perkow reaction [68], which is based on the reaction of halogenated ketones with phosphites, can also be used to prepare vinyl phosphates (Scheme 2b). This is particularly advantageous for the preparation of triple [69,70] and double [71][72][73][74][75][76] electrophilic templates 6 using brominated ketone 5. Cross-coupling reactions are also useful for the introduction of simple fragmentsnamely, the vinyl group.…”
Section: Introductionmentioning
confidence: 99%